2023
DOI: 10.3390/ijms241210094
|View full text |Cite
|
Sign up to set email alerts
|

Cdk4 Regulates Glioblastoma Cell Invasion and Stemness and Is Target of a Notch Inhibitor Plus Resveratrol Combined Treatment

Abstract: Glioblastoma multiforme (GBM) is one of the most aggressive types of cancer characterized by poor patient outcomes. To date, it is believed that the major cause of its recurrence and chemoresistance is represented by the enrichment of GBM stem cells (GSCs) sustained by the abnormal activation of a number of signaling pathways. In this study, we found that in GBM cells, treatment with low toxicity doses of the γ-secretase inhibitor RO4929097 (GSI), blocking the Notch pathway activity, in combination with resver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…The G1-S phase cell cycle checkpoint is mainly controlled by the kinases pathway, and thus improper formation of the cyclin D-1 complexes with CDK 4/6 leads to the promotion of cell-proliferation-involved carcinogenesis. Homozygous deletion of the CDKN2A-p16 INK4α gene in chromosome 9p is one of the three genetic traits of primary GB; in fact, activation of CDK4 is commonly observed in GB cells leading to cell invasion and stemness [ 394 , 395 , 396 , 397 ]. Three CDK4/6 inhibitors, including palbociclib, ribociclib and abemaciclib, have been approved by the FDA as monotherapy for treating breast cancers and are under clinical investigation in GB patients ( Table 3 ) [ 398 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…The G1-S phase cell cycle checkpoint is mainly controlled by the kinases pathway, and thus improper formation of the cyclin D-1 complexes with CDK 4/6 leads to the promotion of cell-proliferation-involved carcinogenesis. Homozygous deletion of the CDKN2A-p16 INK4α gene in chromosome 9p is one of the three genetic traits of primary GB; in fact, activation of CDK4 is commonly observed in GB cells leading to cell invasion and stemness [ 394 , 395 , 396 , 397 ]. Three CDK4/6 inhibitors, including palbociclib, ribociclib and abemaciclib, have been approved by the FDA as monotherapy for treating breast cancers and are under clinical investigation in GB patients ( Table 3 ) [ 398 ].…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…Notch2 transactivates TNC genes and promotes GBM invasion in an RBPJK-dependent manner [81]. Combining Notch inhibitors with resveratrol to target CDK4 can modulate the invasiveness of glioblastoma [82,83]. The downregulation of CBF1, a primary tran-scriptional regulator [84], can reduce Notch signaling activity and thereby attenuate GBM invasion [85].…”
Section: Migration and Invasionmentioning
confidence: 99%
“…The exogenous expression of CDK4 mutants negates the inhibitory effect of RSV and RO4929097 on the motility/invasion of glioblastoma cells and enhances the expression of stemness-specific markers GFAP, CD13.3, and SOX2, and the EMT markers TWIST and SNAIL, as well as the size/formation capability of the neurosphere [83]. The deletion of the α-kinase structural domain in TRPM7 (M7-DK) and the K1648R point mutation (M7-KR) affect Notch activity and the expression of CD133 and ALDH1 in GSCs [113].…”
Section: Regulation Of Stemnessmentioning
confidence: 99%
See 1 more Smart Citation
“…It has the potential to inhibit cell cycle and growth ( Pinchot et al, 2011 ; Yu X. M. et al, 2013 ; Zhang et al, 2014 ), stimulate apoptosis and re-differentiation ( Yu XM. et al, 2013 ), prevent tumor recurrence ( Giordano et al, 2023 ), and impede autophagy ( Giordano et al, 2021 ) in cancer through downregulation of Notch receptors and ligands, including Notch1, Notch2, Notch4, DLL1, DLL4, and Jagged1. These studies indicated that resveratrol could hinder the activation of the Notch pathway through repression of Notch receptors and ligands in several tumors.…”
Section: Phytochemicals Treated Cancers Via Modulating Notch Pathwaymentioning
confidence: 99%